Delay-induced Periodic Oscillations for a Three-enterprise Interaction Model - Feng, Chunhua (European Journal of Applied Sciences, 2024)
In the literature, two-enterprise interaction model with or without delays have been discussed by many researchers. The Hopf bifurcation in such two-enterprise model has been discussed. In this paper, we extend the two-enterprise model to a three-enterprise interaction model with delays. Time delay destroys the stability of the solutions and induces periodic oscillation for this three-enterprise model. Computer simulations are given to demonstrate the proposed results.